A sad portrait of congenital syphilis in the State of Rio de Janeiro. Case report with Polymerase Chain Reaction (PCR) of scrapings from skin lesions and placenta fragment positive for Treponema pallidum - Passos, Felipe Dinau Leal; Guedes , Anderlúcia Corrêa; Melo, Ariela Gomes de; Varella, Renata de Queiroz; Rangel , Isabelle de Carvalho; Carvalho, Ricardo de Souza; Ferry , Fernando Raphael de Almeida; Morais, Julia Sampaio de Souza; Passos, Carolina Varella Leal; Passos, Paula Varella Leal; Lopes, Márcia Quinhones Pires (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Congenital syphilis is a serious public health problem that causes high rates of intrauterine morbidity and mortality, revealing flaws and weaknesses in the health system. Objective: to report a case of congenital syphilis in a university hospital in the Center-South Region of the State of Rio de Janeiro, Brazil. Case report: A pregnant woman, aged between 19 and 23 years old, carrying a Pregnant Woman's Handbook with a record of seven prenatal consultations and a note of the serological reaction for positive syphilis, but without any treatment, hospitalized at the University Hospital of Vassouras (RJ), in labor, gave birth to a newborn (NB) with a clinical picture and serological test of congenital syphilis. The NB required care in an intensive care unit and was discharged 28 days after birth. Scraping of skin lesions of the NB and placenta was performed for analysis by molecular biology (PCR in house) and genetic material of Treponema pallidum was detected. Conclusion: Congenital syphilis is a serious outcome of syphilis during pregnancy, consuming high financial resources and significant emotional distress for the mother, father, the whole family, as well as for the health teams. Our case report was the first that we are aware of in Brazil with a diagnosis by PCR for positive Treponema pallidum of skin scraping and placental fragment. It also showed poor quality prenatal care, a common factor in most cases of CS in our reality.